Subordination Results on Subclasses Concerning Sakaguchi Functions. (19th October 2009) - Frasin, B. A.; Darus, M.
Abstract : We derive some subordination results for the subclasses𝒮 ( α, t ), 𝒯 ( α, t ), 𝒮 0 ( α, t ), and𝒯 0 ( α, t ) of analytic functions concerning with Sakaguchi functions. Several corollaries and consequences of the main results are also considered.